Managing Emotions in the Workplace: It’s Mediating Effect on the Relationship between Organizational Trust and Occupational Stress - Oktuğ, Bige Zeynep (Canadian Center of Science and Education, 2013)
The purpose of this study was to examine the mediating effect of emotion management on the relationship between organizational trust and occupational stress. Since managing emotions in the workplace is a complex issue, this study also aimed to offer an insight into the emotion management of employees. Data were obtained using a survey method from a sample of 167 academics working in different universities in Istanbul. A series of regression analyses was conducted to test the mediating effect of emotion management. It was determined that the ability to manage emotions in the workplace partially mediate the relationship between organizational trust and occupational stress. The results of the study show that managing emotions in the workplace can affect the stress levels of employees. High levels of organizational trust can promote emotion management in the workplace, which in turn can contribute to reducing work-related stress.
Keywords: emotion management; organizational trust; occupational stress